China’s Major Reform in Criminal Law - Cai, DingJian (Columbia Journal of Asian Law, 1997)
On March 14, 1997, the Fifth Session of the Eighth National People’s Congress approved the Reform Bill on Criminal Law, which will produce significant changes to criminal law in China. China’s existing criminal law statute was formulated in 1979 shortly after the Cultural Revolution. It was one of the first of seven groups of laws formulated. Triggered by the lessons learned from the Cultural Revolution, this series of statutory drafting reflected the importance China attributed to the rule of law at that time. A country with a history of a weak legal system, China had little experience in dealing with legal theories. Therefore, the resulting statute focused largely on principles and was comprised of definitions that were unduly formalistic as well as containing many loopholes. In 1982, the Standing Committee of the National People’s Congress began its research on the reform of criminal law, which continued for fifteen years. During this period, the National People’s Congress adopted 22 ordinances and decisions that amended or supplemented the criminal statute. In addition, it adopted 130 articles regarding criminal liabilities in context of civil, economic, and administrative law. The Reform Bill on Criminal Law was formulated out of the accumulated experiences from the enactment of criminal laws over the past 17 years, the research conducted on criminal laws of various foreign countries, and the studies made on modem criminal legislation and developmental trends.